Analisis Teks dan Konteks Pada Kolom Opini Kompas Mewaspadai Ledakan Mudik 2024 - Putri, Valencia Eka Armanda; Iskandar, Dinda Sabrina; Salsabila, Anindya Putri (Jurnal Bahasa dan Sastra, 2024)
Basically, the role of language in communication, whether verbal or written, is very important. Basically, the interaction process can run smoothly if the communicator and the interlocutor understand the context, both the situational context and the sociocultural context of the topic being discussed. The main aim of this analysis is to describe the context and text of the opinion article "Beware of the 2024 Homecoming Explosion" in the Sunday, March 24 2024 edition of the Kompas newspaper by Wihana Kirana Jaya. This research uses a qualitative approach. The data collection technique used is the reading and note-taking technique, which is a method for exploring problems contained in opinion news. The data analysis used in this research went through four stages, namely the stages of data collection, data reduction, data presentation, and drawing conclusions.